Review on building life cycle assessment from the perspective of structural design. Issue 6 (2nd November 2021) - Wang, Zai; Liu, Ying; Shen, Shizhao
ABSTRACT: The resource-related, environmental and ecological problems raised by building construction activities have drawn a wide range of concerns among researches, especially in China. Those problems have become prominent. In last decade, the building life cycle emissions and energy efficiency have been researched widely. Most of the studies focus on the assessment models and emission analysis based on the available project data and statistical data. Very few of them study the emissions from the view of structure design, which can reduce the building emission at source. This review summarizes and examines different models proposed for the building life cycle assessment, focusing on the model scopes, assumptions, and their applications from the view of structure design. A great attention is given to the data used in the current studies. Finally, a variety of future research directions of building life cycle assessment are discussed.